Dataset on the use of biostimulants in strawberry cultivation under tropical conditionsMendeley Data - Maria Celina Villagra Luraschi; Noelia Isabel Godoy Medina; Victoria Rossmary Santacruz Oviedo; Romina Burgos Rotela; Cipriano Ramón Enciso-Garay (Data in Brief)
In tropical conditions, due to high temperatures, the use of plant management practices is necessary to increase productivity. For strawberry production, biostimulants can promote an increase fruit quality and production. These substances can promote plant growth, increase stress tolerance, promote root growth and nutrient absorption, increase stress tolerance and improve fruit quality. In some Latin American countries, including Paraguay, the strawberry production system is carried out by family farming, with poor management of seedlings, production technology, health problems and lack of access to new varieties. The objective of this work was to determine how different doses of biostimulants affect seven varieties of strawberry. The experiment was conducted at the Universidad Nacional de Asunción, Facultad de Ciencias Agrarias (UNA/FCA), during March–July 2022. The treatments consisted of a combination of seven varieties of strawberry with three levels of biostimulants. The varieties were Sabrina, Camino Real, Festival, Sweet Charlie, Dover, Francesita, Early Bright and the doses of biostimulant applied were 0 ml/L, 1 ml/L and 2 ml/L. The experimental design was subdivided into plots with a bifactorial arrangement (7x3), where factor I was the three doses and factor II was the seven varieties. Each treatment had four repetitions, and each experimental unit consisted of four plants. Evaluated parameters included, total and commercial fruit number per plant, total and commercial fruit mass, total and commercial yield per square meter, diameter and length of the fruit, content of soluble solids totals, titratable acidity, pH and fruit firmness. Data were analyzed using analysis of variance (ANOVA) followed by Tukey´s test at the 5 % significance level. Dover and Festival varieties achieved excellent productivity (4.63 and 3.17 kg m² respectively), regardless of the treatment doses.